Crenças, atitudes e preconceito de profissionais de saúde frente à vulnerabilidade em saúde sexual de lésbicas - Lima, Michael Augusto Souza de (2020)
The general objective of this thesis was to analyze the beliefs, attitudes and prejudice of health professionals, facing the vulnerability in sexual health of lesbian cis women, and the existence of campaigns to promote the sexual health of these women. Therefore, it starts from the thesis that there are elements of an individual nature, such as beliefs and attitudes of health professionals; social, such as prejudice and discrimination; and programmatic, such as the insufficiency and ineffectiveness of the current health campaigns, which associates may reflect in the care provided by health professionals in the sexual health care of lesbians. To confirm this thesis, the present research was divided into four chapters, each corresponding to a study. Chapter I: It was an exploratory and descriptive study, with qualitative design, which allowed to identify and analyze the beliefs of doctors, nurses, nursing technicians and health agents who work in Nursing Units. Family Health about the affection-sexual practices of lesbians. The sample was stratified by convenience, so 31 (thirty-one) participants of both genders are part of the study. For data collection, a sociodemographic questionnaire and the Free Word Association Technique (TALP) were used. For data analysis, the software SPSS (descriptive statistics) and IRaMuTeQ (similarity and prototypical analysis) were used. Most of the words evoked by the participants pointed to the possibility of positive beliefs about lesbian women. However, evocations also emerged that pointed out disapproving beliefs about female homosexual behavior, considering this practice as something wrong, unusual and deviant. Some participants attributed the sexual vulnerability of lesbians to perversion, betrayal and even as a result of divine punishment. Chapter II: It was an exploratory and descriptive study, with qualitative design, which allowed the investigation and analysis of the attitudes of doctors, nurses, nursing technicians and health agents who work in Units of Family Health about the affection-sexual practices of lesbians. The sample was stratified by convenience, so 31 (thirty-one) participants of both genders are part of the study. For data collection, two questionnaires were used, a sociodemographic and an attitudes questionnaire composed of five questions. For data analysis, the software SPSS (descriptive statistics) and the ThematicCategorical Content Analysis technique were used. The results indicated the existence of a dichotomy of attitudes, which were favorable and unfavorable. It was possible to perceive the influence of attitudes on the services provided, since they are part of the perception that professionals have about the figure of the lesbian user, and everything associated with it, such as their demands, specificities, ways of preventing STIs. and health promotion. Chapter III: It was an exploratory and descriptive study, with qualitative design, which allowed the investigation and analysis of the positions of doctors, nurses, nursing technicians and health agents who work in Health Units of the Family on the existence of prejudice and discrimination against lesbian users in health services. The sample was composed of the least participants in Study II. 196/5000 For data collection, two questionnaires were used, a sociodemographic one and the Priming technique, preceded by a questionnaire composed of five questions related to the plot presented. For data analysis, the software SPSS (descriptive statistics) and the Thematic Categorical Content Analysis technique were used. The results indicated the existence of a dichotomy that divided the positions into two opposing groups: unfavorable and favorable to the conduct of the character of the doctor who denied medical care to the character for being a lesbian. Chapter IV: This was an exploratory, cross-sectional and documentary study carried out with materials in the public domain available on the Internet in order to carry out documentary analysis of materials from campaigns carried out by and / or in partnership with the government, prepared in Brazil, aimed at health professionals and / or users, to promote the sexual health of lesbians. Keywords related to the theme were used to locate the sites. The time range from 2004 to 2019 was used as a reference for the delimitation of documents. A total of 7 documents were found. The results showed that part of the materials located have superficial and little detailed guidelines, in addition to inaccurate information about the specific needs of lesbians. Deficiencies in the way these materials are made available to professionals and / or to the lesbian population were also noticed. It was considered that the studies carried out supported the proposed thesis, that elements that make up the three dimensions of the concept of health vulnerability, can really reflect, in different degrees and circumstances, in the care provided by health professionals in sexual health care of lesbians.